2009
DOI: 10.1016/j.lfs.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of late sodium current by protein kinase A in R1623Q mutant of LQT3

Abstract: Aims-In the type 3 long QT syndrome (LQT3), shortening of the QT interval by overdrive pacing is used to prevent life-threatening arrhythmias. However, it is unclear whether accelerated heart rate induced by β-adrenergic agents produces similar effects on the late sodium current (I Na ) to those by overdrive pacing therapy. We analyzed the β-adrenergic-like effects of protein kinase A and fluoride on I Na in R1623Q mutant channels.Main methods-cDNA encoding either wild-type (WT) or R1623Q mutant of hNa v 1.5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…R1632C I Na availability in both the atrium and the ventricle, whose resting membrane potentials are approximately À90 mV, is likely to be substantially reduced (Online Supplemental Figure S2), although the current reduction caused by the hyperpolarizing shift in voltage dependence of inactivation might be enhanced in our experimental condition. 28 A pronounced reduction of I Na in both the atrium and the ventricle may be associated with multiple electrophysiological phenotypes (BrS, AT, and SND) observed in our patient. An increased HV interval and QRS duration could also be attributable to the R1632C mutation.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…R1632C I Na availability in both the atrium and the ventricle, whose resting membrane potentials are approximately À90 mV, is likely to be substantially reduced (Online Supplemental Figure S2), although the current reduction caused by the hyperpolarizing shift in voltage dependence of inactivation might be enhanced in our experimental condition. 28 A pronounced reduction of I Na in both the atrium and the ventricle may be associated with multiple electrophysiological phenotypes (BrS, AT, and SND) observed in our patient. An increased HV interval and QRS duration could also be attributable to the R1632C mutation.…”
Section: Discussionmentioning
confidence: 51%
“…Of note, repetitive depolarizing pulses rapidly attenuated R1632C I Na compared with WT I Na (Online Supplemental Figures S3B and S3C), and β-adrenergic stimulation augments the frequency-dependent reduction of I Na . 28 These findings may explain the clinical phenotypes of our patient such that AT preferentially occurred during exercise or was induced by high-frequency atrial stimuli during isoproterenol infusion.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…PKA stimulation has also been reported to augment late Na + currents in mutant Na + channels (ΔKPQ, D1790G and R1623Q). [22][23][24] One of these three SCN5A mutations, D1790G, is located in the C-terminal domain. Its effect on the augmentation of late Na + currents was reportedly diminished by the co-presence of SCN5A-S36A and -S525A mutations, which lost phosphorylation sites in the N-terminus and in the cytoplasmic I-II loop, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The g NaL was fitted by Tsurugi et al [16] and Maltsev et a experiments, they measured an I NaL /I NaF approximately, and g NaL was fitted in our m The conductance yielded 0.055 mS/µF. It i the ratio does not change with temperature experimental data demonstrated that the inactivation is modified by temperature, fo multiplied τ h by the factor Q10 (2.2), so τ h y 37ºC [8;18].…”
Section: ( )mentioning
confidence: 91%